Macrophage Cholesteryl Ester Mobilization and Atherosclerosis - Ghosh, Shobha (2009)
Accumulation of cholesteryl esters (CE) stored as cytoplasmic lipid droplets is the main characteristic of macrophage foam cells that are central to the development of atherosclerotic plaques. Since only unesterified or free cholesterol (FC) can be effluxed from the cells to extracellular cholesterol acceptors, hydrolysis of CE is the obligatory first step in CE mobilization from macrophages. This reaction, catalyzed by neutral cholesteryl ester hydrolase (CEH), is increasingly being recognized as the rate limiting step in FC efflux. CEH, therefore, regulates the process of reverse cholesterol transport and ultimate elimination of cholesterol from the body. In this review, we summarize the earlier controversies surrounding the identity of CEH in macrophages, discuss the characteristics of the various candidates recognized to date and examine their role in mobilizing cellular CE and thus regulating atherogenesis. In addition, physiological requirements to hydrolyze lipid droplet-associated substrate and complexities of interfacial catalysis are also discussed to emphasize the importance of evaluating the biochemical characteristics of candidate enzymes that may be targeted in future to attenuate atherosclerosis.